Potential Optimization For Bumdes Development (Case Study: Duarato Village, Lamaknen District, Belu Regency) - Nikson Tameno; Olivia L.E. Tomasowa; Desembri C. Nope (CV. AFDIFAL MAJU BERKAH, 2023)
This research aims to provide information to BUMDes to create business units that can manage and utilize village potential to advance community businesses while at the same time developing BUMDes businesses. In this study there are several problem formulations including: (1). How to optimize the potential of Duarato village that can be developed by BUMDes Selomon. (2). What is the strategy of the Duarato village government in optimizing the potential it has to develop businesses carried out by BUMDes. The research method used is a qualitative social research method with an FGD pattern to obtain primary and secondary data and carried out with a SWOT analysis to get the right strategy for BUMDes to add business units by utilizing the village's potential. The results of the research can be taken several strategies for developing the potential of Duarato village, namely First, increasing the productivity and quality of onion farming and cattle farming. Second, Improving agricultural and animal husbandry systems. Third, Improving human resources. Fourth, improving the quality of infrastructure and the environment .